2022
DOI: 10.1111/dmcn.15211
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported impact of developmental stuttering across the lifespan

Abstract: To examine the phenomenology of stuttering across the lifespan in the largest prospective cohort to date. Method: Participants aged 7 years and older with a history of developmental stuttering were recruited. Self-reported phenotypic data were collected online including stuttering symptomatology, co-occurring phenotypes, genetic predisposition, factors associated with stuttering severity, and impact on anxiety, education, and employment. Results: A total of 987 participants (852 adults: 590 males, 262 females,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…geneticsofstutteringstudy.org.au). We invited 1,071 participants from the Australian arm of this cohort with a selfreported history of stuttering described in the work of Boyce et al (2022) for deep phenotypic characterization.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…geneticsofstutteringstudy.org.au). We invited 1,071 participants from the Australian arm of this cohort with a selfreported history of stuttering described in the work of Boyce et al (2022) for deep phenotypic characterization.…”
Section: Participantsmentioning
confidence: 99%
“…Participants self-enrolled through the website (http://www.geneticsofstutteringstudy. org.au), where they provided their consent and completed survey questions (Boyce et al, 2022).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The covert consequences range from shame and frustration to social anxiety. Stuttering can severely limit the scope of interpersonal verbal communication and set up barriers that impact education and employment outcomes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Boyce et al 2 sought to assess the impact of stuttering based on a variety of self‐report measures. Consistent with prior studies, 3 they found that individuals who stutter exhibit their own unique phenotype reflecting their unique personal characteristics and experiences with stuttering.…”
mentioning
confidence: 99%